The Influence of Leadership on the Effectiveness of Livestock Farmer Groups and P3A Banda Tangah in Managing Rice Field Irrigation in Lubuk Sikarah District Solok City - Nelvi, Yusmi (Journal of Animal Nutrition and Production Science, 2023)
This research aims to determine the influence of group leader leadership, group effectiveness, and group leader leadership on the effectiveness of the Banda Livestock Farmers and Water Users Farmers Association (P3A). Tangah in irrigation management in lowland rice cultivation. This research was conducted using a survey method in IX Korong Village, Lubuk Sikarah District, Solok City. The research sample consisted of 65 respondents randomly selected from members of the Banda Tangah P3A group. The research results show that the leadership of the P3A group leader is in the medium category, and the effectiveness of the Banda Tangah P3A group is in the high category. The leadership of the P3A group leader has a significant influence on the effectiveness of the Banda Tanga P3A group in managing irrigation in the Banda Tangah P3A, Lubuk Sikarah District, Solok City.